UTAUT UNTUK MEMAHAMI TINGKAT PENERIMAAN PENGGUNA SISTEM OPERASIONAL APLIKASI PT.SWADHARMA SARANA INFORMATIKA SENTRA OPERASI CILACAP - Fiby Nur Afiana; Eka Tripustikasari (Universitas Sriwijaya, 2020)
PT.Swadharma Sarana Informatika is a provider of Information Technology and Automated Teller Machine (ATM) management facilities, using an Application Operating System (SOA) to support website-based or online financial reports 24 hours a day. In the implementation of input there are complaints by users or users of the SOA application, within a period of two months it is often slow in responding to it because the data on the server is full so the backup needs to be held by the central SOA server maintenance team, when the server used to manage resources experiencing problems will cause the cessation of all activities on the network. The user factor is a very important factor to consider in implementing a new system, empirical studies are needed to evaluate the real conditions of users for new applications that are applied. UTAUT (Unified Theory of Acceptance and Use of Technology) is a method that is widely used by researchers to measure how successful and user acceptance of implementing an information technology-based system. This method is considered suitable for understanding the level of user acceptance with the variables used are (performance expectancy), business expectations (effort expectancy), social influence (social influence), facilitating conditions (faciliating conditions), Gender (Gender) and user behavior ( Use Behavior) of SOA acceptance level. Validity Test, Reliability Test, Normality Test using Kolmogonov-Smirnov One Sample Method, Linearity Test, Heteroscedasticity Test and Simple Linear Regression Test are used to determine the results of this study, the results obtained indicate that there is a significant positive effect on Performance Expectancy Variables ), Effort Expectancy Variables, Social Influence Variables and Faciliating Conditions Variables have a positive effect on Behavioral Intention.